2013
DOI: 10.1161/strokeaha.111.000382
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Corticospinal Tract Fractional Anisotropy Predicts Long-term Motor Outcome After Stroke

Abstract: Background and Purpose— Nearly 50% of patients have residual motor deficits after stroke, and long-term motor outcome is difficult to predict. We assessed the predictive value of axonal damage to the corticospinal tract indexed by diffusion tensor imaging fractional anisotropy for long-term motor outcome. Methods— Consecutive patients with middle cerebral artery stroke underwent multimodal MRI, including diffusion tensor imaging ≤12 hours, 3 days, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
105
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 15 publications
9
105
0
3
Order By: Relevance
“…10 Measurement of CST integrity with diffusion tensor imaging (DTI) 11 has been proposed both by assessment of decreases in FA distal to the stroke area and by the quantification of a decrease in the number of CST fibers, as an index of fiber degeneration (Wallerian degeneration). 12,13 In most previous work, including the one by Byblow et al, 10 these measurements were primarily obtained weeks or months after stroke 14,15 precluding their use for early prognostication. At the subacute stage, Feng et al 16 quantified the overlap of the acute stroke with a canonical CST derived from DTI of healthy controls instead of using DTI in patients.…”
Section: April 2016mentioning
confidence: 99%
“…10 Measurement of CST integrity with diffusion tensor imaging (DTI) 11 has been proposed both by assessment of decreases in FA distal to the stroke area and by the quantification of a decrease in the number of CST fibers, as an index of fiber degeneration (Wallerian degeneration). 12,13 In most previous work, including the one by Byblow et al, 10 these measurements were primarily obtained weeks or months after stroke 14,15 precluding their use for early prognostication. At the subacute stage, Feng et al 16 quantified the overlap of the acute stroke with a canonical CST derived from DTI of healthy controls instead of using DTI in patients.…”
Section: April 2016mentioning
confidence: 99%
“…MRI can also be used to derive biomarkers of the motor system after stroke 10. Worse upper limb motor recovery and outcomes are predicted by greater stroke lesion load on descending corticomotor pathways,11 and greater asymmetry in fractional anisotropy along the corticospinal tracts 12, 13, 14, 15. To date no single clinical measure or neurological biomarker has been able to accurately predict motor recovery or outcome for all patients, and therefore approaches using combinations of measures and biomarkers are needed 6…”
Section: Introductionmentioning
confidence: 99%
“…1,4 In addition, diffusion tensor imaging (DTI) studies have reported that the use of fractional anisotropy (FA) of corticospinal tract (CST) alone to predict future motor function of the upper extremity in patients with stroke in the acute period is also unreliable. [8][9][10][11] Researchers have proposed that more accurate prognoses may be made by combining behavioral tests with magnetic resonance imaging (MRI) determinations of the functional or structural integrity of the ipsilesional corticomotor tract. 12,13 However, it has been reported that on the base of initial impairment, adding functional MRI task-related brain activation patterns (during hand closure task) to their prediction model did…”
mentioning
confidence: 99%